The Simplest Memristor Circuit With Hyperchaos - Liu, Xingce; Wang, Jinpeng (Frontiers in Physics, 2022)
In recent years, with the in-depth study of the memristor, meminductor, and memcapacitor, the fourth basic element has been developed vigorously. The chaotic circuit including the meminductor, memcapacitor, and memristor is designed in this study. The equation of state for the chaotic system is obtained according to Kirchhoff’s volt–current law, and the mathematical model of the chaotic system is obtained through dimensionless processing. The stability of the equilibrium point is analyzed in detail, and the dynamic behaviors of the system are analyzed by traditional methods such as LEs and bifurcation diagram. Moreover, some special phenomena exist in the system, such as state transition and coexistence of attractors. Finally, the circuit is implemented by DSP to prove the realizability of chaotic circuit.